Tela’ah Fi’il Tsulatsi Mujarrad Dalam Surah Yasin: Definisi, Distribusi Dan Fungsinya - Hayati (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the fi’il tsulatsi mujarrad (trilateral basic verbs) in surah Yasin based on their morphological patters and functional distribution within the contekxt of the verses. Fi’il tsulatsi mujarrad refers to basic verbs in arabic consisting of three original root letter without any additions and serves as a fundamental element in the science of sharf (arabic morfologi). Using a descriptive qualititave verbs (fi’il mazid) in surah Yasin. The findings indicate that the past tense form (fi’il Madhi) is more dominant than the present tense form (fi’il mudhari). Several frequently recurring verbs highlight their essential role in conveying the massages of the Al-Qur’an. The analysis also reflects on actions and serves as a referense for understanding the basic meanings in morphological analysis. This study is expected to contribute to a deeper understanding of the qur’anic language and support Arabic language learning through the Al-Qur’an.